Kadar Protein Terlarut Dan Kualitas Tempe Benguk Dengan Penambahan Ampas Tahu Dan Daun Pembungkus Yang Berbeda - Setyawan, Arief Vendy; , Triastuti Rahayu, S.Si, M.Si (2015)
Mucuna tempe with addition of tofu residue is an innovation in make of tempe. Wrapper leaf tempe used include banana leaves, hibiscus leaves and leaf teak, which each have different specific. The purpose of this research was to determine the levels of soluble protein and mucuna tempe quality with addition tofu residue and wrapper different leaf. The method used in this reasearch is Completely Randomized Design (CRD) with two factors, factor 1 is ratio mucuna seed : tofu residue (A0=100%:0%, A1=80%:20%, A2=75%:25%, A3=70%:30%) and factor 2 is wrapper leaf (B1=banana leaves, B2=hibiscus leaves, B3=teak leaves) with 12 treatment. The result of this reasearch has showed that addition tofu residue and wrapper different leaf can affect the levels of soluble protein mucuna tempe. The highest soluble protein in the treatment of mucuna tempe with a ratio of 70% mucuna seed : 30% tofu residue and teak leaf wrappers (A3B3) that is equal to 4.781%. The lowest soluble protein in the treatment of mucuna tempe with a ratio of 80% mucuna seed : 20% tofu residue and banana leaf wrappers (A1B1) that is equal to 2.637%. The quality of mucuna tempe with the addition tofu residue and different wrapper leaf has texture rather loud-loud, the flavor of fresh tempeh-bit unpleasant and white color flat-uneven until browned.